DNA adducts and lung cancer risk: a prospective study - Peluso, M; Munnia, A; Hoek, G; Krzyzanowski, M; Veglia, F; Airoldi, L; Autrup, H; Dunning, A; Garte, S; Hainaut, P; Malaveille, C; Gormally, E; et al. (American Association for Cancer Research, 2005)
Objectives were to investigate prospectively the ability of DNA adducts to predict cancer and to study the determinants of adducts, especially air pollutants. DNA adducts were measured in a case-control study nested in the European Prospective Investigation into Cancer and Nutrition (EPIC) investigation. Cases included newly diagnosed lung cancer (n = 115), upper respiratory cancers (pharynx and larynx; n = 82), bladder cancer (n = 124), leukemia (n = 166), and chronic obstructive pulmonary disease or emphysema deaths (n = 77) accrued after a median follow-up of 7 years among the EPIC former smokers and never-smokers. Three controls per case were matched for questionnaire analyses and two controls per case for laboratory analyses. Matching criteria were gender, age, smoking status, country of recruitment, and follow-up time. Individual exposure to air pollution was assessed using concentration data from monitoring stations in routine air quality monitoring networks. Leukocyte DNA adducts were analyzed blindly using 32P postlabeling technique. Adducts were associated with the subsequent risk of lung cancer, with an odds ratio (OR) of 1.86 [95% confidence interval (95% CI), 0.88-3.93] when comparing detectable versus nondetectable adducts. The association with lung cancer was stronger in never-smokers (OR, 4.04; 95% CI, 1.06-15.42) and among the younger age groups. After exclusion of the cancers occurring in the first 36 months of follow-up, the OR was 4.16 (95% CI, 1.24-13.88). A positive association was found between DNA adducts and ozone (O3) concentration. Our prospective study suggests that leukocyte DNA adducts may predict lung cancer risk of never-smokers. Besides, the association of DNA adduct levels with O3 indicates a possible role for photochemical smog in determining DNA damage.